Human gamma-trace, a basic microprotein: amino acid sequence and presence in the adenohypophysis. - Grubb, A (1982)
The amino acid sequence of human gamma-trace, a basic microprotein without known function, was determined by automated Edman degradations of the carboxymethylated polypeptide chain and of fragments obtained by cyanogen bromide treatment and tryptic digestion after blocking of lysine residues. The single polypeptide chain contained 120 residues, and the calculated Mr was 13,260. A proline residue at position 3 was partly hydroxylated. The presence of gamma-trace in a significant proportion of the cells in the anterior lobe of simian and human pituitary glands was demonstrated by immunohistochemical procedures with a rabbit antiserum against human gamma-trace. The tissue localization and amino acid sequence of gamma-trace indicated that this protein is connected with the peptidergic gastroenteropancreatic neuroendocrine system.